Evaluation the Pulmonary Tuberculosis Control Program with Strategy DOTS in Puskesmas Tanah Kalikedinding Surabaya - Noveyani, Adistha Eka; Martini, Santi (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTStrategy DOTS is the tuberculosis control programs. The program has implemented in Tanah Kalikedinding Health Center and has expected to reach CDR â¥ 70% and SR â¥ 85%, which closely related to the management of health centers. This study aimed to evaluate the implementation of the DOTS program in health center whose the results associated with indicators of tuberculosis. This was a descriptive design study with the population was all pulmonary specialist, tuberculosis officers and laboratory personnel and pulmonary tuberculosis patients. The number of Tuberculosis patient respondents was 32 respondents. Samples were chosen using purposive sampling. Data collected by interview questionnaire and checklist. The variables were the finding case, the TB treatment, the enabling factor and inhibiting factor, recording and reporting, and result of tuberculosis indicators. This study resulted that CDR in 2013 was 112% already reached the national target â¥ 70%. This success related to the finding case almost all patients > 2 weeks of cought and all (100%) patients were examinated sputum and diagnosed according to the steps of tuberculosis diagnosis in Indonesia Department of Health guidelines. While SR in 2013 was 65.5% did not reach the target â¥ 85%. It was caused of there are patients who did not have a taking drug observer (PMO). All (100%) patients ever forgot taking anti tuberculosis drugs. Change in schedule of visit to the continuation phase be 2Ã/month caused patients to forget taking anti tuberculosis drugs. The enabling factor was counseling routinely by health care workers in health center. Inhibiting factor was distance to health center by majority (65,5%) patients were > 1 km. So they needed vehicle to go to the health center. Recording and reporting using electronic systems and being reported by online. So it is expected all TB patients were expected have a taking drug observer and optimizing the role of the a taking drug observer to increase success rate.Keywords: DOTS strategy, Case Detection Rate, Success Rate, evaluation, Â Â Â Â Â Â Â Â Â Â Tuberculosis